Curcumol attenuates liver sinusoidal endothelial cell angiogenesis via regulating Glis‐PROX1‐HIF‐1α in liver fibrosis. (2nd March 2020) - Yang, Xiang; Wang, Zhimin; Kai, Jun; Wang, Feixia; Jia, Yan; Wang, Shijun; Tan, Shanzhong; Shen, Xikun; Chen, Anping; Shao, Jiangjuan; Zhang, Feng; Zhang, Zili; et al.
Abstract: Objective: Hepatic sinusoidal angiogenesis owing to dysfunctional liver sinusoidal endothelial cells (LSECs) accompanied by an abnormal angioarchitecture is a symbol related to liver fibrogenesis, which indicates a potential target for therapeutic interventions. However, there are few researches connecting angiogenesis with liver fibrosis, and the deeper mechanism remains to be explored. Materials and Methods: Cell angiogenesis and angiogenic protein were examined in primary LSECs of rats, and multifarious cellular and molecular assays revealed the efficiency of curcumol intervention in fibrotic mice. Results: We found that curcumol inhibited angiogenic properties through regulating their upstream mediator hypoxia‐inducible factor‐1α (HIF‐1α). The transcription activation of HIF‐1α was regulated by hedgehog signalling on the one hand, and the protein stabilization of HIF‐1α was under the control of Prospero‐related homeobox 1 (PROX1) on the other. A deubiquitinase called USP19 could be recruited by PROX1 and involved in ubiquitin‐dependent degradation of HIF‐1α. Furthermore, our researches revealed that hedgehog signalling participated in the activation of PROX1 transcription probably in vitro. Besides, curcumol was found to ameliorate liver fibrosis and sinusoid angiogenesis via hedgehog pathway in carbon tetrachloride (CCl4 ) induced liver fibrotic mice. The protein expression of key regulatory factors, PROX1 and HIF‐1α, was consistent with the Smo, the marker protein of Hh signalling pathway. Conclusions: In this article, we evidenced that curcumol controlling LSEC‐mediated angiogenesis could be a promising therapeutic approach for liver fibrosis.